Antecedents and outcome of social competency: a toolkit for Malaysia millennials’ entrepreneurs / Nur Melissa Mohammad Faisal Wee … [et al.] - Mohammad Faisal Wee, Nur Melissa; Sadik, Mohd Zaki; Hassian, Ummi Kalsum; Wan Hasan, Wan Hasmat; Abdul Rahim, Fahmi (Division of Research and Industry Linkages, 2017)
It is estimated that by 2025, the number of millennials generation will add up to 75% of the global workforce and their response towards entrepreneurship will change the future of the workplace. In fact, the number of young entrepreneurs has increased in Malaysia and a comprehensive study of the social competency to be successful and competitive in their business is required. In the context of this study, structural social capital and relational social capital are the antecedents of entrepreneurs' social competency. Meanwhile dimensions within social competency which are social perception, social adaptability, expressiveness, and impression management are claimed to impact the performance of entrepreneur firms which acts as a measure of successful entrepreneurs, Specifically, the study focuses on the non-financial performance as outcome of this study.